Building your research team: Insights on hiring, assembling, and leading research teams - Paul Rothenberg, MD, MS; Shiv Patel, BS; Anahita Dua, MD, MBA, MSc; Samantha D. Minc, MD, MPH (JVS-Vascular Insights, 2025)
Background/Objective: Teams are extremely important for productive vascular surgery research. Surgeons are uniquely poised to be at the forefront of meaningful research teams. Methods and Conclusions: We discuss team science and leadership in leading scientific research teams. We also discuss poignant tenets for building and maintaining a successful vascular surgery research team.